Investigation of magnetic flux density on conducting and non-conducting cylindrical surface using magnetic sensor. (2022) - Vadde, Anusha; Meghana, T.V.; Sahana, K.M.; Keerthi, T.G.; Gouthami, Y.
Abstract: This paper highlights the investigation of the magnetic flux density on the conducting and non-conducting surfaces by providing magnetic and electric field as a source of excitation. Measuring the leakage magnetic flux density and flux within low frequencies on conducting and non-conducting surfaces is useful for the non-invasive measurement methods. The Helmholtz coil is used to excite the cylindrical surface in two ways: magnetic and electric field excitation. The Hall Effect sensor is used to detect the strength of magnetic flux density on the cylindrical surface. Direction of flux lines, distribution of magnetic flux density and electric field around the surface explained through the simulation results. The results are graphically plotted by varying the current for the magnetic field excitation and by varying the voltage for electric field excitation. Hall voltage is varying linearly with increase in current and constant with increase in voltage for the non-conducting cylindrical surface for various locations of cylindrical surface. Simultaneously, Hall voltage is linearly increases and decreases for the excitation of voltage and current for the conducting cylindrical surface is presented through the graphs.